Ziphius cavirostris bio inspired acoustic antenna. Finite element analysis and experimental validation. (May 2016) - Guadalupe, V.L.; Militello, C.; Recuero, M.
Abstract: One way to amplify an incoming signal is to design a receiver that couples with the signal frequency. In this study a resonant system made of a belt, one part exposed to the incoming signal and the other part inserted in a protected cavity is investigated. The cavity is shaped like a tapered horn in order to obtain maximum amplification at the horn tip. A finite element model based on displacement fields for the acoustic fluid and the belt is developed. The moving surfaces are coupled in such a way that the coupled stiffness and mass matrices are symmetric. Different resulting coupling modes are analysed. A prototype is constructed in order to verify the numerical results. The experimental and numerical results agree to within 6%. The desired amplification inside the cavity is obtained and the time exposure necessary to reach a stationary wave inside the cavity is measured. The design is a simplified, bio inspired, representation of a Ziphius cavirostris lower jaw bone and its surrounding fat cavity.